Evaluation of relationship between reproductive health literacy and demographic factors in women - shahnaz kohan; fatemeh mohamammadi; Maryam Yazdi; azam dadkhah (Mashhad University of Medical Sciences, 2018)
Background and objective: Introduction: Health literacy is the ability of people to acquire, understand and use health information that is necessary to decide on this field.  Since, reproductive health literacy promotion is known as one of the strategies to meet reproductive health goals in different groups of women. This study aimed to evaluate the relationship between reproductive health literacy and demographic factors in women of Isfahan city. Methods:This study was a descriptive-analytic research that was evaluated women's reproductive health literacy and its related factors in Isfahan using the questionnaire of health literacy scale for women of reproductive age. Sampling method was easy and 235 women were enrolled in the study. Data analysis was performed using the software SPSS20. Results: The average age of these women was 27/8 ± 11/01 years, most were high school graduates and married. The reproductive health literacy score was desirable in 91% of women and two variables of marital status and age had correlation with reproductive health literacy scores. Conclusion: The results showed marital status and age were two related factors to women's reproductive health literacy level. Accordingly, the reproductive health literacy scores of women younger than 25 years old and unmarried women were lower than other groups. Paper Type:Research Article.